Roles of Glutathione s-transferease in maize (Zea mays L.) under cold stress (Research in Agriculture Livestock and Fisheries, 2015)
Glutathione S-transferease (GST) activities involved in antioxidant defense and methylglyoxal detoxification were investigated in the seedlings of a Bangladeshi maize variety, BARI hybrid maize-7, to understand the protecting mechanism under cold stress condition. The activities of glutathione S-transferase (GST) increased, while the activities of catalase (CAT) decreased with the duration of stress. The western blot analysis of the dominant GST revealed that it significantly accumulated during the stress period. The continual increase in H2O2 contents along with reduced redox state and activities suggested their roles in maintaining the glutathione homeostasis. The accumulation of GST with the content of H2O2 suggested its detoxification roles for organic hydroperoxides during chilling stress. Considering all, glutathione S-transferase (GST) enzymes showed protective role in maize from oxidative damages under Chilling condition.Res. Agric., Livest. Fish.2(1): 9-15, April 2015